New species of the genus Encyonema (Cymbellales, Bacillariophyta) from the Descoberto River Basin, Central-western Brazil - Da Silva, Weliton Jose; Souza, Maria Das Gracas Machado De (Phytotaxa, 2015)
Two new species of Encyonema are described from Central-western Brazil, bringing the total number of species in this genus recorded in Brazil to 45. Encyonema menezesiae has lanceolate valves with the ends subcapitate to rostrate-capitate, whereas E. candangense has linear valves with indistinct ends. The two species show deep alveoli, linear foramina, and densely areolate striae. These characteristics, together with the narrow valves, distinguish E. menezesiae and E. candangense from related taxa. The new species occurred in slightly acid and mostly oligotrophic waters. Similar aquatic environments in this region are being drastically affected by the use of biocides and fertilizers for agriculture. The description of these two species and their ecological preferences may provide useful information for the preservation of aquatic systems and their communities in Brazil.